Euro Area Policies : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper assesses the youth unemployment problem in advanced European economies, especially the euro area. Youth unemployment rates increased sharply in the euro area after the crisis. Much of these increases can be explained by output dynamics and the greater sensitivity of youth unemployment to economic activity compared with adult unemployment. Labor market institutions also play an important role, especially the tax wedge, minimum wages, and spending on active labor market policies. The paper highlights that policies to address youth unemployment should be comprehensive and country specific, focusing on reviving growth and implementing structural reforms.